Time complexity in rejang language stemming - Sastya Hendri Wibowo; Rozali Toyib; Muntahanah Muntahanah; Yulia Darnita (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
Stemming is the process of separating the root word from an affixed word in a sentence by separating the base word and affixes which can consist of prefixes (prefixes), insertions (infixes), and suffixes (suffixes). Between one language and another, there are differences in the algorithm, especially the stemming process, in morphology. The time complexity of the Rejang algorithm is determined based on the affix group. To find out the time complexity of the stemming algorithm in the Rejang language using the method of making a digital word dictionary of the Rejang language, studying and analyzing the morphology of the Rejang language, making the Rejang language stemming algorithm based on the results of the Rejang language morphology analysis, analyzing the algorithm's performance and calculating the time complexity of the stemming results. The result of this research is to produce an efficient and effective Rejang Language stemming algorithm, where efficiency is indicated by the algorithm's time complexity of O(log n), and the effectiveness is shown from the results of accuracy of 99% against the test of 9000 affixed words. This accuracy value indicates that the over stemming and under stemming processes are 1%. Test results on 15 text documents with an average stemming failure rate of 1%.